The treatment of H.pylori infected adults and children in Volgograd: pharmaco-epidemilological investigation - Magnitskaya O.V.; Ponomareva Ju.V.; Ryazanova A.Ju.; Yefimova A.A.; Chechetkina Je.M.; Idelbaeva E.S.; Bukina N.Ju.; Volodina L.A.; Kartashova T.R.; Gorjushkina A.A.. (Саратовский научно-медицинский журнал, 2014)
This article represents results of pharmacoepidemiological research of H.pylori eradication treatment of adults and children in Volgograd. The aim was to determine H. pylori pharmacotherapy stereotypes and compare with international experts' recommendations. Material and Methods. There were analyzed CRFs of 94 adults and 132 children with H.pylori associated diseases in Volgograd region. Results. There were identified mistakes of treatment regimes and eradication control principles. Conclusion. The treatment of H.pylori infected adults and children in Volgograd does not match to international experts' recommendations.